Maternal control and early child dysregulation: Moderating roles of ethnicity and child delay status. Issue 2 (29th April 2016) - Caplan, B.; Baker, B.L.
Abstract: Background: Maternal controlling behaviour has been found to influence child development, particularly in behavioural and emotional regulation. Given the higher rates of interfering parent control found in mothers of children with developmental delays (DD) and Latina mothers, their children could be at increased risk for behavioural and emotional dysregulation. While studies generally support this increased risk for children with DD, findings for Latino children are mixed and often attributed to cultural models of child rearing. The present study sought to determine the moderating roles of child DD and mother ethnicity in determining the relationships between two types of parent control (supportive directiveness and interference) and child dysregulation over time. Methods: The present study, involving 178 3‐year old children with DD ( n  = 80) or typical development ( n  = 98), examined observed parent control (directive versus interfering) of Latina and Anglo mothers as it relates to change in preschool child dysregulation over 2 years. Results: Interfering parent control was greater for children with DD and also for Latino mothers. Supportive directive parenting generally related to relatively greater decline in child behaviour and emotion dysregulation over time, while interfering parenting generally related to less decline in child behaviour dysregulation over time. In Anglo but not Latino families, these relationships tended to vary as a function of child disability. Conclusions: Parent directives that support, rather than deter, ongoing child activity may promote positive regulatory development. These results particularly hold for children with DD and Latino families, and have implications for parenting practices and intervention.